Indikasi Mineralisasi Tipe Porfiri di Daerah Sumbersari, Kompleks Pengunungan Kulon Progo, Purworejo, Indonesia - Verdiansyah, Okki; Muharif, Damas; Sukadana, I Gde (BRIN Publishing, 2020)
Kulon Progo Mountain is Sunda-Banda Arc magmatism product composed of an old andesite formation. Sumbersari Area is part of the Gajah volcanic, which is the oldest rock of Kulon Progo volcanics. Indication of porphyry type mineralisation has been found in the area which makes the area interested for further research. The research methodologies are geological mapping, petrography and ore microscopy, and geochemical analysis using XRF and ICP-MS. Geology of the area located in central-proximal facies of Khuluk Gajah, consist of microdiorite, quartz-microdiorite, andesite, basaltic-dioritic andesite intrusions, and limestone. Hydrotermal alteration is developing into certain groups like illite-sericite ± secondary biotite, epidote-actinolite-calcite ± illite, epidot-calcite ± illite, and illite-sericite ± quartz. Some mineralisation phases are developed like epidote-actinolite followed by magnetite-chalcopyrite mineralisation, biotite-magnetite-chalcopyrite-bornite phase and the late phase of sericite-clay-pyrite replacing the entire system. Geochemical analysis on altered rocks show Cu-Au mineralisation indication ranging from 491-1,447 ppm (0.14%) and 0.02-0.3 ppm respectively, with Cu:Au ratio is 1.01. Geochemical characteristic shows strong correlation of Cu to Au.